2017
DOI: 10.3389/fpsyg.2017.00791
|View full text |Cite
|
Sign up to set email alerts
|

Reading Words or Pictures: Eye Movement Patterns in Adults and Children Differ by Age Group and Receptive Language Ability

Abstract: This study was conducted to explore the differences in the degree of attention given to Chinese print and pictures by children and adults when they read picture books with and without Chinese words. We used an eye tracker from SensoMotoric Instruments to record the visual fixations of the subjects. The results showed that the adults paid more attention to Chinese print and looked at the print sooner than the children did. The stronger the children’s receptive language abilities were, the less time it took them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For example, in the human-computer interaction and usability study, Poole et al (2004) indicated that increased gaze fixation counts on an interested visual area showed that it was more essential and more noticeable to the subject than other visual areas. An et al (2017) also reported that gaze fixation during a reading task reflects the level of word awareness. When the degree of attention given to the target increases, the related fixation counts also increase.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in the human-computer interaction and usability study, Poole et al (2004) indicated that increased gaze fixation counts on an interested visual area showed that it was more essential and more noticeable to the subject than other visual areas. An et al (2017) also reported that gaze fixation during a reading task reflects the level of word awareness. When the degree of attention given to the target increases, the related fixation counts also increase.…”
mentioning
confidence: 98%
“…Clearly, eye tracking provides information of where in the TEIL environment a student’s gaze is fixed as well as the frequency and the duration of that gaze. Coupled with gaze location, which reveals various levels of attraction of elements of the environment, these characteristics could be modeled as indicators of test engagement, which, in turn, might reflect the magnitude of cognitive load a student exhibits when solving test items (e.g., An, Wang, & Sun, 2017; Poole, Ball, & Phillips, 2004; Roy-Charland, Saint-Aubin, Klein, & Lawrence, 2006; Yi, Lu, & Ma, 2017).…”
mentioning
confidence: 99%
“…Third, age is also a key factor affecting the effectiveness and comprehension of reading with picture books. In recent years, many studies have explored teaching effectiveness of picture books when used by adults to enhance language proficiency and to broaden their worldviews (Bang 2000;Murayama et al 2015;An, Wang, and Sun 2017;Wei and Ma, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On average, the U.S. books had 21.17 pages (ranging between 10 and 57 pages) and the Japanese books had 16.83 pages (ranging between 11 and 26 pages). We focused on the visual contents of illustration rather than the wording of each image segment as similar to the previous study (Tsai et al, 2007) because young children spent most of the time on the illustration than the wording of the picture books (An et al, 2017). The target ages listed by the library were used for Japanese books.…”
Section: Sampling Booksmentioning
confidence: 99%
“…In the current study, we analyzed the visual contents of the U.S. and Japanese picture books for young children to see whether visual contents follow a similar trend found in previous studies that might encourage the attentional differences observed in young children and adults. We focused on the visual contents of illustration, rather than the wording of picture books because young children spent most of the time on the illustration than the wording of the picture books (An et al, 2017). Based on Miyamoto et al (2006), if the visual environment influences the differences in attention, the picture books from the U.S. would be less visually crowded than Japanese picture books.…”
mentioning
confidence: 99%